Reducing Students’ Pronunciation Anxiety by Utilizing WhatsApp Group in Learning English Consonant Sounds - Vivi Aulia (Universitas Negeri Makassar, 2018)
This research aims at describing the utilization of WhatsApp group to reduce students’ pronunciation anxiety in learning English consonant sounds. It is conducted to the first semester of English Department students at STKIP PGRI Banjarmasin batch 2018 in Pronunciation Practice course. The instruments of this research are the documentation of students’ scores on voice records sent to WhatsApp group and the questionnaire. Both the instruments are analyzed quantitatively. The documentation of students’ voice records is analyzed to see their progress of practicing English consonant sounds during eight meetings. Meanwhile, the questionnaire is analyzed to get their impressions and personal feelings whether the use of WhatsApp group help them to reduce their anxiety as well as fear of making error in pronunciation practice. The result of students’ voice record documentation shows that there are 56% students who have good scores, 42% students have enough scores, and 5% of students have fair scores. It indicates that the result of students’ pronunciation practice needs to be improved. The students should carry out regular practice to get maximal pronunciation ability. The result of questionnaire shows that there are 78% of them state that WhatsApp group helps them much in learning, feel enjoy, have self-confidence as the result of having more relax after involving on class discussion using WhatsApp group.